2012
DOI: 10.4314/ajcem.v13i2.3
|View full text |Cite
|
Sign up to set email alerts
|

The Sero-Prevalence of Parvovirus Antibodies among Children with Sickle Cell Anaemia in Zaria

Abstract: Parvovirus is an erythrovirus that infects red cell precursors in individuals with conditions characterised by a high red cell turnover like sickle cell anaemia and thalassaemia. Arthritis, vasculitis, carditis, bone marrow failure, and the slapped cheek appearance have been associated with Parvovirus B19 infection. Recurrent blood transfusion is a risk factor for the B19 serotype of Parvovirus infection, with the P antigen as the mediator for erythroid invasion presenting as transient erythroblastopaenia (TEB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
1
2
4
Order By: Relevance
“…High positivity observed in this study among full time housewives could also be due to the fact that women are always in contact with children both at home and outside the home. This finding does not conform to the work of Ujo et al (8) who did not find any association between occupation and HPVB19 among parents of children in their study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…High positivity observed in this study among full time housewives could also be due to the fact that women are always in contact with children both at home and outside the home. This finding does not conform to the work of Ujo et al (8) who did not find any association between occupation and HPVB19 among parents of children in their study.…”
Section: Discussioncontrasting
confidence: 99%
“…This increasing seropositive rate with increasing age is consistent with the work of Girei in Jos (2) and reports from other countries (11,5,15). However, the results contrast that of Ujo and colleagues whose study reported that seropostivity did not increase with age (8). This discrepancy could be due to the fact their study was carried out in children with sickle cell disease whereas this study was carried out among all kinds of patients in the general population aged from 0-70 years.…”
Section: Discussioncontrasting
confidence: 82%
“…The study also found that there is no sex association in the seroprevalence of the virus in both SCA patients and healthy blood donors. This is in agreement with the findings of Ujo et al (15) and Teuscher et al (16) in their separate studies.…”
Section: Haematological Parameterssupporting
confidence: 94%
“…18 Kim et al in their study on the epidemiology of parvovirus in sickle cell disease patients reported an increase in seroprevalence with age (19).In this study, we found a peak age prevalence to be 18 -24 years in SCA patients and blood donors. This is higher than that reported by Ujo et al (15).…”
Section: Table3: Seroprevalence Of Igg and Igm Antibodies By Age In Scontrasting
confidence: 61%
See 1 more Smart Citation